EVALUASI KEWAJARAN SCHEDULE KONTRAKTOR MENGGUNAKAN WORK BREAKDOWN STRUCTURE (WBS) DAN MICROSOFT PROJECT (STUDI PADA PROYEK PEMBANGUNAN SDN 5 SOKONG, TANJUNG, LOMBOK UTARA) - ZAEDAR GAZALBA; I GEDE PUTU WARKA; LALU WIRAHMAN W (Universitas Mahasaraswati K. Mataram, 2022)
Scheduling in the sense of a construction project is a tool to determine the activities needed to complete a project in a certain sequence and time frame, where each activity must be carried out so that the project is completed on time at an economical cost. In this study, the researcher evaluates the reasonableness of the contractor's schedule with the researcher's schedule from the Microsoft Project.This study was conducted to analyze the reasonableness of the contractor's schedule whether the contractor's schedule is in accordance with the reality on the ground. The data used in this study is secondary data in the form of working drawings and s curves. Analysis of this schedule using the Microsoft project application. Data analysis is carried out by making basic assumptions of building construction, creating a scope of work, making work durations, making relationships between jobs and then analyzing them in the Microsoft project application.The criteria for the fairness of the schedule are seen from the order of work, work items and work duration. The results showed that of the four contractor schedules at SDN 5 Sokong that met the fair criteria, only the CV UTAMA schedule